Chronic subdural haematomas: a single-centre experience developing an integrated care pathway. (4th July 2017) - Bapat, Smita; Shapey, Jonathan; Toma, Ahmed; Platt, Louise; Luoma, Astri Maria Valpuri
Abstract: Objective: To improve quality of care for patients presenting with chronic subdural haematoma (CSDH) by introducing a multi-disciplinary integrated care pathway. Summary background: CSDH is a common neurological condition. Incidence rises with age and currently affects around 58/100 000 people over 70 years. Six-month mortality is high (26%), however integrated care pathways have been shown to improve patient outcomes in other surgical subspecialties. Materials and methods: A baseline retrospective audit completed in 2012 identified areas for improvement in patient management. Stakeholder meetings were held with subsequent development and implementation of a patient care pathway. A post-implementation prospective audit was completed between January and October 2015. Data collected: patient demographics, medical co-morbidities, use of anti-platelet and anti-coagulant medication, timing of surgery, length of hospital stay, morbidity and mortality data, and reaccumulation rate. Results: Patient groups were similar with a high incidence of multi-morbidity. The key areas targeted for improvement included enhanced pre-operative optimisation and time to surgery. Implementation of the patient care pathway significantly increased the number of patients undergoing surgery within 24 hours of admission (43% vs. 75%, p = 0.0006) but length of hospital stay did not change. Operative morbidity and mortality remained similar and there was no significant difference in CSDH reaccumulation rate. Conclusion: Our patient care pathway appears to have improved pre-operative care and significantly increased the proportion of patients undergoing surgery within 24 hours of admission. Difficulties were encountered with changing existing practice. Prospective research is required to demonstrate the full benefits, which may include a reduction in health and social care costs.